Understanding Literal and Nonliteral Illocutionary Acts in Communicative Speech (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores illocutionary acts in communicative speech, focusing on literal and nonliteral expressions. It discusses how speakers convey meaning through direct speech acts like constatives and indirect acts like sarcasm and metaphor. Drawing on Austin's Speech Act Theory, it examines how context shapes interpretation, emphasizing the complexities of communicative intent.